Sustainable Development of E-commerce in the Post-COVID Times: A Mixed-Methods Analysis of Pestle Factors - Adriana Dima; Elena Radu; Ecaterina Milica Dobrota; Adrian Otoiu; Alina Florentina Saracu (Amfiteatru Economic, 2023)
E-commerce represents an essential part of modern business, with a significant growth in recent years. Recent events, such as the COVID-19 pandemic, have led to a surge in online shopping and a rapid shift towards e-commerce, creating a new normal in the retail industry. To succeed in this changing landscape, it is important for organisations to understand the Political, Economic, Social, Technological, Legal, and Environmental (PESTLE) factors that influence e-commerce. This exploratory research applies a mixed-methods approach to identify the PESTLE factors that affect the e-commerce landscape in post COVID times. The study was conducted by developing a questionnaire for organisations that use e-commerce in their operations and was applied to a sample of 309 Romanian firms, with mixed methods such as principal component analysis (PCA) and multinomial logistic regression. The results suggest that the pandemic has intensified the adoption of e-commerce, and businesses are focused on expanding their online presence and leveraging new technologies to enhance the customer experience. The findings contribute to understanding the PESTLE factors that influence e-commerce and can provide valuable insights for policymakers, businesses, and other stakeholders seeking to make informed decisions that facilitate the sustainable development of e-commerce. Limitations of this research include restricting the sample to Romanian organisations, with results that may be less relevant for other economies. Also, the study focuses on PESTLE factors, leaving other possible influences on e-commerce in the post-COVID period unaddressed.
Keywords: L81; 330; e-commerce; PESTLE analysis; internet; retail